Development and evaluation of a complex of studies to increase the frequency of bending vibrations of modern passenger car bodies - A. N. Skachkov; S. L. Samoshkin; S. D. Korshunov; D. A. Nikiforov; D. A. Romashov (Вестник Научно-исследовательского института железнодорожного транспорта)
Investigations of the frequency of bending vibrations of the car bodies of 61-4440 model range, which includes compartment cars, staff cars, non-compartment cars, coach cars, restaurant cars and others, are described. The bodies of all cars of this model range have the same overall dimensions and are made of corrosionresistant steels (stainless) with flat corrugated sheathing of the lower (under the window) belt.To assess the influence of the design features of stainless steel bodies on its bending stiffness and the parameters of bending vibrations in the vertical plane, a computational and experimental complex of works was carried out.After analyzing the calculation results and experimental data, proposals were developed and implemented to increase the bending stiffness of the metal body structure with stainless steel skin. To check the implemented proposals, complex tests were carried out to determine the parameters of bending vibrations of the metal structure of the experimental body. The tests were carried out according to the combined method developed by the authors. For this, a vibrator, installed in the console parts of the body, and impulse excitation were used.The results of testing the metal structure of the experimental body in comparison with the results of testing the car bodies of 61-4440 model range showed the effectiveness of the implemented proposals, namely: increasing the frequency of the first tone of bending vibrations by 18 %; decrease in the amplitude of vertical vibrations of the body structure at the frequency of the first tone from 12 to 50 %; decrease in the amplitude of the vertical accelerations of the metal structure of the body during oscillations at the frequency of the first tone approximately by 2 times; significant reduction in horizontal acceleration in the area of the middle section walls. The effectiveness of the implemented proposals for increasing the bending stiffness of the metal structure of the experimental body allows recommending them for the entire model range of 61-4440 cars.